Ralph Compton [large type] : Texas Hill : a Ralph Compton novel - Compton, Ralph; Robbins, David, 1950- (Wheeler Publishing, 2016)
Owen Burnett tries to better his financial situation by rounding up cattle in the Texas Hill Country with a business partner not realizing that his partner has no plans of sharing the cash.